Of Valuable Agricultural Characters In F1 Plants Of Medium Fiber Cotton Gen Collection Lines - Xayitova Shaxlo Davlatovna (Zien Journals, 2023)
In the article Inheritance of valuable husbandry traits was determined in F1 plants of medium fiber cotton gene collection lines
Keywords: combination; polyploidy; introgressive line